PENERAPAN PERANGKAT BIO-BATERAI BERBAHAN AMPAS KOPI DAN PEMANFAATANNYA SEBAGAI MEDIA PEMBELAJARAN FISIKA SMA DI KOTA TOMOHON - Ishak Pawarangan; Widya Tumewu; Vicky Mawuntu (LP2M Universitas Ibrahimy, 2025)
Coffee is one of the most popular caffeinated beverages globally, with a continuously growing commercial demand. This community service project aims to implement a coffee ground-based bio-battery device and utilize it as a learning medium for high school physics in Tomohon, in collaboration with the Tomohon Physics Teacher Working Group (MGMP Fisika). The program was conducted using Service Learning methods, which integrate community service with academic learning to achieve meaningful outcomes for both students and the community. The implementation consisted of five stages: socialization, training, technology implementation, mentoring, and evaluation, along with program sustainability efforts. The outcomes achieved include the availability of a coffee ground bio-battery prototype, a renewable energy learning module, and increased knowledge and skills among partners, as shown by pretest and posttest results. Additional outputs include the publication of articles in electronic and print media, activity implementation videos, and a guide module for developing and using the bio-battery prototype. Furthermore, an additional outcome was obtaining copyright for the technology. This project produced a bio-battery device that serves not only as an alternative energy source but also as an effective and relevant physics learning medium, enhancing students' awareness of renewable energy and environmental sustainability.